The Importance of Soft Skills Training in the Curriculum of Higher Education - Shekhawat, Anupama (Prabandhan: Indian Journal of Management, 2012)
Soft skills are personal attributes that enhance an individual’s interactions, job performance and career prospects. Unlike hard skills, which are about a person’s skill set and ability to perform a certain type of task or activity, soft skills are interpersonal and broadly applicable. Soft skills are often described by using terms often associated with personality traits, such as: Optimism, Common Sense, Responsibility, A Sense of Humor, Integrity; and abilities that can be practiced (but require the individual to genuinely like other people) such as: Empathy, Teamwork, Leadership, Communication, Good Manners, Negotiation, Sociability, the Ability To Teach. Now-a-days, nobody wishes to gain knowledge to be a scholar as in the previous ages. In fact, knowledge has become a stepping stone to land up a good paying job, and to get a reputed position in the society. Because of these reasons, higher education now demands a transformation to meet the elevated desires of the students. Irrespective of the professional qualification, today’s professionals need to possess a high Soft Skills quotient, apart from domain knowledge in order to succeed in this competitive era. Due to the great importance of soft skills, some of the colleges have introduced it as their add-on course. However, many of them are yet to introduce Soft Skills in their prescribed curriculum. This article deals with the importance of Soft Skills in the curriculum of Higher Education and its role in making the student placement worthy. This study is a comparative analysis between students who are regularly exposed to Soft Skills sessions and those not exposed to the same, with respect to their overall Soft Skills.